2020
DOI: 10.1051/ocl/2020010
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two Moroccan watermelon seeds oil varieties by three different extraction methods

Abstract: The purpose of this study is to assess and evaluate the physicochemical properties of the seed oils of two Moroccan varieties of watermelon “Citrullus lanatus” extracted by three different techniques, a mechanical process using cold press, and two chemical processes using a Soxhlet apparatus and a sonotrode ultrasound assisted extraction (UAE) using n-hexane. The total phenolic compounds (TPC) and antioxidant properties against the DPPH radicals (2,2-diphenyl-1-picrylhydrazyl) were also studied. The seed oils … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
1
11
0
1
Order By: Relevance
“…Similarly, in WSO oil, the predominant fatty acids were palmitic, stearic, oleic and linoleic acids (Dumitru and Tutunea, 2017;Ok and Yilmaz, 2019;Petchsomrit et al, 2020). The same trend was observed by Ouassor et al (2020) when studying two varieties of watermelon. According to Zarifikhosroshahi and Ergun (Zarifikhosroshahi and Ergun, 2021), the order of importance of fatty acid contents in WSO is as follows: palmitic, oleic, stearic, and linoleic acids.…”
Section: Fatty Acid Composition Of the Oilssupporting
confidence: 67%
See 2 more Smart Citations
“…Similarly, in WSO oil, the predominant fatty acids were palmitic, stearic, oleic and linoleic acids (Dumitru and Tutunea, 2017;Ok and Yilmaz, 2019;Petchsomrit et al, 2020). The same trend was observed by Ouassor et al (2020) when studying two varieties of watermelon. According to Zarifikhosroshahi and Ergun (Zarifikhosroshahi and Ergun, 2021), the order of importance of fatty acid contents in WSO is as follows: palmitic, oleic, stearic, and linoleic acids.…”
Section: Fatty Acid Composition Of the Oilssupporting
confidence: 67%
“…Besides, the AVof WSO found in this current study is in the range of the contents of the oils obtained from the two varieties of Moroccan watermelon seeds using various extraction methods (1.40 ± 0.03 and 2.80 ± 0.06 mg KOH/g oil). Nevertheless, these authors observed greater PV (6.00 ± 0.08, 4.0 ± 0.67 and 3.80 ± 0.20 meq O 2 /kg oil) (Ouassor et al, 2020).…”
Section: Physicochemical and Quality Parameters Of The Oilsmentioning
confidence: 71%
See 1 more Smart Citation
“…The oil content of watermelon seeds is in the range of 10-35%, varying depending on the genotype (Ziyada and Elhussien, 2008;Mahla et al, 2018). Watermelon seed oil is reported to be a good source of essential fatty acids, carotenoids, tocopherols, thiamine, flavonoid, riboflavin, and other phenolic substances, quantities of which vary depending on watermelon variety and extraction method (Ouassor et al, 2020). Linoleic acid is the most abundant fatty acid found in watermelon seed oil irrespective of variety.…”
Section: Introductionmentioning
confidence: 99%
“…Although the oil content of watermelon seeds vary according to the genotype, it is in the range of 10-35% (Ziyada and Elhussien, 2008;Mahla et al, 2018). Watermelon seed oil is a rich source of essential fatty acids, the amount of which varies depending on the extraction method and cultivar (Ouassor et al, 2020). Linoleic acid is the most abundant fatty acid in watermelon seed oil, regardless of the cultivar.…”
Section: Introductionmentioning
confidence: 99%